Ceramic-metal composite wear parts
By using prefabricated ceramic-metal composite inserts in wear parts and forming ceramics in combination with self-propagation exothermic reactions, the problem of difficult to obtain high-concentration ceramic reinforcement areas in the prior art is solved, and higher wear resistance and stability are achieved.
Patent Information
- Application Number
- CN202180038712.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-29
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-03-25
AI Technical Summary
The prior art is difficult to obtain reinforced areas containing very high concentrations of ceramics, and the reinforced portions are prone to unnecessary movement during casting.
Prefabricated ceramic-metal composite inserts, containing high concentrations of metal carbides, nitrides, borides or intermetallic alloy microparticles, are used to form ceramics through self-propagation exothermic reactions to ensure that the reinforcement part is fully fixed during the casting process.
The reinforcement area of high concentration ceramics is achieved in the wear part, which improves the wear resistance and stability of the part and avoids unnecessary movement of the reinforcement part.
Smart Images

Figure CN115867401B_ABST
Abstract
Description
Technical Field
[0001] Subject matter of the invention
[0002] The present invention relates to cast wear parts. More particularly, the present invention relates to a wear part comprising a portion reinforced with a predetermined geometry having a prefabricated ceramic insert inserted into an infiltrative structure containing precursor reactants that form the ceramic by a self-propagating exothermic reaction during the casting process.
[0003] The invention also proposes a method for obtaining said wearing part with its reinforcement structure. Background Art
[0004] Current state of the art
[0005] Ore mining and crushing equipment, especially grinding and crushing equipment, is subject to many restrictions in terms of impact and wear resistance.
[0006] In the field of aggregate, cement and ore processing, wear parts include ejectors and anvils of vertical shaft crushers, hammers and beaters of horizontal shaft crushers, cones for crushers, tables and rollers of vertical mills, liners and elevators of ball or rod mills. As regards ore mining equipment, mention may be made in particular of oil sands pumps or drills, mining pumps and excavator teeth.
[0007] Well known in the art are composite wear parts manufactured by casting, comprising a portion reinforced by a ceramic produced in situ during casting by a self-propagating exothermic reaction initiated by the casting heat.
[0008] Document WO 03 / 047791 describes a wear part having a series of ceramics of the carbide, nitride, boride or intermetallic alloy type formed in situ during a self-propagating exothermic reaction (SHS) The reaction is initiated by the casting of the metal matrix and propagates rapidly, reaching temperatures exceeding 2000°C.
[0009] Documents WO 2010 / 031660; WO 2010 / 0311661; WO 2010 / 031663 and WO 2010 / 031662 propose wear parts with titanium carbide formed in situ by a self-propagating exothermic reaction. This involves a graded reinforcement structure in which the reactants are aggregated in the form of millimeter particles assembled in a padding with an inorganic glue to form an infiltrative geometry during a self-propagating exothermic reaction initiated by casting. This technique produces a structure with alternating areas of low and high concentrations of titanium carbide spheres, the high concentration areas being located where the precursors of the reactant particles (in this case carbon and titanium) of the titanium carbide forming reaction are located.
[0010] Controlling the in-situ ceramic-forming reaction that occurs at around 2500°C is difficult, which is why "moderators" such as iron powder are often used to make the reaction less violent and thus better controlled. However, the disadvantage is that the ceramic concentration is diluted and changes the hardness of the entire structure. Therefore, the concentration of carbides, nitrides and borides, as well as intermetallic alloys, is limited by this phenomenon.
[0011] It is also problematic to keep the reactant powders in the form of millimeter particles or the inserts compacted according to a predetermined geometry during the casting process, which can lead to unwanted movement of the reinforcement. Summary of the invention
[0012] Purpose of the invention
[0013] The present invention aims to overcome the disadvantages of the prior art, in particular the difficulty in obtaining a reinforced region comprising a very high concentration of ceramic (for example greater than 50% by volume).
[0014] The invention also aims to integrate regions in the form of inserts of predetermined geometry having a high concentration of ceramic into a structure permeable to the ceramic precursor reactants, while being able to ensure that the reinforcements are adequately fixed in the mold during casting of the wear part.
[0015] Summary of the Invention
[0016] The invention discloses a wear part comprising a reinforcement portion comprising a ferrous alloy reinforced with metal carbides, nitrides, borides or intermetallic alloys, wherein the reinforcement portion comprises an insert having a predetermined geometry, the insert comprising micronized particules of metal carbides, nitrides, borides or intermetallic compounds, which are preformed and encapsulated in a first metal matrix (10), the insert being inserted into an infiltrated reinforcement structure comprising periodically alternating high and low concentrations of micronized particules of metal carbides, nitrides, borides or intermetallic alloys produced by agglomerated grains comprising the reactants required for an in-situ exothermic self-propagating synthesis initiated during casting of a ferrous alloy, the ferrous alloy forming a second metal matrix, the second metal matrix being different from the first metal matrix.
[0017] Preferred embodiments of the present invention include at least one or any suitable combination of the following features:
[0018] - the metal of the ceramic particles used for the insert is titanium, preferably the insert mainly comprises microparticles of titanium carbide;
[0019] - the insert contains a concentration of up to 90% by volume and at least 30% by volume, preferably at least 40% by volume and particularly preferably at least 50% by volume of metal carbides, nitrides, borides or intermetallic elements;
[0020] - the first metal matrix to which the ceramic particles of the insert are bonded consists essentially of nickel, a nickel alloy, cobalt, a cobalt alloy or an iron alloy different from the casting alloy constituting the second metal matrix;
[0021] the insert comprises particles of metal carbides, nitrides, borides or intermetallic alloys having an average size D50 of less than 80 μm, preferably less than 60 μm and particularly preferably less than 40 μm;
[0022] - the prefabricated insert and the area in which the ceramic is formed during casting comprises micrometer gaps containing different metal matrices;
[0023] - the reinforcing structure consists of alternating millimetre areas of high ceramic concentration, resulting from the aggregation of reactants that have reacted, and millimetre areas of very low ceramic concentration, forming millimetre gaps infiltrated by the second metal matrix, ie the cast metal;
[0024] The reinforcing structure also comprises millimeter particles of alumina, zirconium oxide or an alumina-zirconium oxide alloy.
[0025] The present invention also discloses a method for manufacturing a wear part according to the present invention, comprising the following steps:
[0026] - providing a mould comprising a cavity of a wear part having a predetermined geometry of the area to be reinforced;
[0027] - an intimate mixture of powders in the form of millimetre granules, optionally mixed with a moderating powder at least partially surrounding one or more prefabricated inserts of defined geometry and enriched in metal carbides, nitrides, borides or intermetallic compounds, for reaction in a self-propagating exothermic reaction in the form of millimetre granules as precursors of metal carbides, nitrides, borides or intermetallic compounds, introduced and positioned in the zone to be reinforced;
[0028] - casting a ferroalloy into a mould, said liquid ferroalloy initiating said self-propagating exothermic reaction resulting in the formation of metal carbides, nitrides, borides or intermetallic compounds in said precursor pellets;
[0029] - forming in the reinforced region of the wear part an alternating macro-microstructure of periodic millimeter areas respectively enriched and depleted in metal carbides, nitrides, borides or intermetallic elements infiltrated by the second metal matrix produced by casting, the overall structure at least partially surrounding the one or more inserts.
[0030] According to a preferred embodiment of the method according to the invention, the insert with the predetermined geometry produced before casting the wearing part has the following properties:
[0031] - the insert is manufactured by powder metallurgy;
[0032] - An intimate mixture of powders for reaction in the form of millimeter pellets in a self-propagating exothermic reaction consisting of carbon, titanium, a binder and optionally a moderating powder.
[0033] The invention also discloses the main application in the form of an impactor, anvil, cone or grinding roller. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A wear part according to the invention is schematically shown, having a zone reinforced by cylindrical inserts made of prefabricated ceramic-metal composites. These inserts contain ceramic microparticles incorporated in a first metal matrix. These inserts are surrounded by a structure of periodically alternating millimeter areas of high and low concentrations of ceramic, resulting from the SHS reaction of millimeter particles of precursor reactants infiltrated by a cast metal forming a second metal matrix, which initiates an in-situ exothermic reaction forming micronized ceramic particles next to the prefabricated ceramic inserts. The second metal matrix is different from the first metal matrix.
[0036] Figure 2 Schematically shown are details of a reinforcement insert according to the invention consisting of a prefabricated cylindrical insert of a ceramic-metal composite material fixed in a structure of millimeter grains of a precursor reactant infiltrated by a cast metal which initiates an in situ exothermic reaction forming ceramic particles next to the prefabricated ceramic insert.
[0037] Figure 3 Schematically shown is a movable cone of a crusher having a predetermined area to be reinforced by a prefabricated cylindrical insert of a ceramic-metal composite material surrounded by a structure of millimetre particles permeable to a precursor reactant.
[0038] Figure 4A hammer of a crusher is schematically shown having a predetermined area to be reinforced by a prefabricated cylindrical insert of a ceramic-metal composite material surrounded by a structure of millimetre particles permeable to a precursor reactant.
[0039] Figure 5 The beater of a crusher is schematically shown having a predetermined area to be reinforced by a prefabricated cylindrical insert of a ceramic-metal composite material surrounded by a structure of millimetre particles permeable to a precursor reactant.
[0040] Figure 6 A digger tooth is schematically shown having a predetermined area to be reinforced by a prefabricated cylindrical insert of a ceramic-metal composite material surrounded by a structure of millimeter particles infiltrated with a precursor reactant.
[0041] Figure 7 is a photograph of a real reinforcement structure, on which one can see that the ceramic-metal composite insert is placed in a three-dimensional structure of reactive ceramic precursor particles that will be transformed into ceramic during the casting process.
[0042] Figure 8 A prior art impactor is shown after wear. The contour lines represent the outline of the component before wear.
[0043] Fig. 9 The impactor according to the invention is shown after wear. The contour lines here also represent the components before wear. The insert surrounded by the infiltrated three-dimensional structure is evident. It has a better wear resistance.
[0044] Fig.10 Schematically shown is a method for measuring the Feret diameter (minimum Feret diameter and maximum Feret diameter). The Feret diameter is used in this method to obtain the average size of the ceramic-metal particles (as explained below)
[0045] Numbered list
[0046] 1: Composite wear parts reinforced by ceramic compositions at the locations most exposed to wear.
[0047] 2: A reinforcement structure of predetermined geometry infiltrated by a cast metal, which structure, prior to infiltration, contains the reactants necessary to form a ceramic based on metal carbides, nitrides, borides or intermetallic alloys by a self-propagating exothermic reaction.
[0048] 3: A prefabricated ceramic-metal composite insert, comprising a metal matrix different from the cast metal, is integrated into an infiltrative structure and the entire structure is placed in a mold designed to receive the cast metal.
[0049] 4: Detail of the reinforcement structure showing areas with low concentrations of formed ceramic particles.
[0050] 5: Detail of the reinforcement structure showing areas with a high concentration of formed ceramic particles.
[0051] 6: Casting metal.
[0052] 7: Spherical particles of metal carbides, nitrides, borides or intermetallic elements formed in situ during the casting process by a self-propagating exothermic reaction. The reaction is initiated by the heat of casting.
[0053] 8: Micrometer gaps between ceramic particles infiltrated by the cast metal (steel or cast iron) of the wear part or composed partly of the moderating metal.
[0054] 9: Prefabricated ceramic particles, which may account for up to 90% of the total volume of the insert, but which account for at least 10% of the volume of the insert, preferably at least 20% or 30%, particularly preferably 40% or 50%. The insert may be manufactured by any technique, but is preferably manufactured by powder metallurgy.
[0055] 10: A first metal matrix which acts as a binder for the ceramic particles of the prefabricated insert. The first metal matrix is different from the second metal matrix formed by the cast metal infiltrating the infiltrative structure.
[0056] 11: Schematic diagram of a movable cone of a crusher comprising a reinforcement structure according to the invention.
[0057] 12: Schematic diagram of a hammer of a crusher comprising a reinforcement structure according to the invention.
[0058] 13: Schematic diagram of a beater of a crusher comprising a reinforcement structure according to the invention.
[0059] 14 : Schematic diagram of an excavator tooth including a reinforcement structure according to the present invention. DETAILED DESCRIPTION
[0060] Detailed description of the invention
[0061] The invention discloses a conventional casting-made wear part with enhanced wear resistance. The invention more particularly relates to a wear part comprising a reinforcement section of predetermined geometry having a pre-made ceramic insert of several centimeters in size inserted into a permeable three-dimensional structure consisting of aggregated millimeter particles and forming a periodic alternation of particles and millimeter gaps. The particles contain the reactants required to form the ceramic by a self-propagating exothermic reaction during the casting process.
[0062] The permeable structure thus consists of aggregates of millimeter particles with an average size of 0.5-10 mm, preferably 0.7-6 mm and particularly preferably 1-4 mm. The gaps between the particles depend on the degree of compaction and the size of the particles, but are of the order of one millimeter or a fraction of one millimeter. The millimeter particles comprise a homogeneous mixture of reactive powder and, if necessary, mitigating powder, and can be aggregated / compacted or held in a metal container using a binder in order to geometrically define a reinforced area of the wear part.
[0063] The prefabricated ceramic inserts for being held by the three-dimensional structure of the aggregated particles may have any shape, preferably cylindrical or approximately cylindrical. In the case of a cylindrical shape, the dimensions of these prefabricated ceramic inserts are 3-50 mm in diameter, preferably 6-30 mm, more particularly 8-20 mm, and 5-300 mm in height, preferably 10-200 mm, particularly 10-150 mm.
[0064] The invention thus describes a wear part which is reinforced on its most stressed side or sides, on the one hand, by a preformed ceramic (ceramic-metal composite), generally obtained by metallurgy of a powder comprising a first metal matrix for bonding ceramic microparticles, and on the other hand by a ceramic formed in situ during the casting of steel or liquid cast iron (second metal matrix), the first metal matrix being completely independent of the second metal matrix, which enables it to be managed in a customized manner.
[0065] This technology makes it possible to conveniently and securely position a prefabricated insert having a defined geometry and enriched with metal carbides, nitrides, borides or intermetallic alloys and comprising a metal matrix independent of the metal matrix produced by casting. This metal matrix, present before casting the wear part, is present from the outset in the ceramic-metal composite insert, which is integrated into an infiltrative structure formed by aggregated millimetric particles (filling) containing the reactants required to form the ceramic material necessary for the self-propagating exothermic reaction and which is formed during the casting of the wear part by initiating SHS (English: "self-propagating high-temperature synthesis": https: / / en.wikipedia.org / wiki / Self-propagating_high- temperature_synthesis ) reaction.
[0066] Contrary to the practice in the prior art, preformed ceramic-metal composite inserts, for example cylindrical or frustoconical inserts, are used in this part. Such inserts may consist, for example, of titanium carbide, titanium nitride or chromium carbide in a minimum concentration of 40% by volume in a first metal matrix containing, for example, iron, manganese, nickel or cobalt (for example a composition of the DIN 1.3401 or DIN 2.4771 type), which is "encapsulated" in an infiltrative structure, for example made of aggregates of millimeter particles of a mixture of carbon and titanium, which aggregates may be diluted with a moderator such as iron or steel powder (for example 45CrMoV67 steel), which is converted into TiC formed in situ by a self-propagating exothermic reaction during the casting of the wear part. The TiC formed in situ and at least partially infiltrated by the cast metal (second metal matrix) creates a "hybrid" structure with areas of high TiC concentration at the location of the geometric insert, prefabricated with its own metal matrix (first metal matrix comprising Ni, Mn, Co, steel, Ni alloy), at least partially surrounded by a structure in which the ceramic has been formed in situ and in which the interstices have been infiltrated by the cast metal of the wear part. This therefore involves an area reinforced by a prefabricated ceramic-metal insert surrounded by periodically alternating millimeter areas of high and low ceramic concentrations resulting from a structure of aggregated reactant particles (e.g. Ti+C) which are converted into titanium carbide by the SHS reaction during the casting process.
[0067] The expression "TiC" should not be interpreted in the strict chemical sense of the term, but rather in the crystallographic sense as titanium carbide, since titanium carbide has a wide composition range with a stoichiometric C / Ti ratio of 0.47 to 1. The same applies to other ceramics such as nitrides and borides, whose stoichiometry can vary relatively greatly.
[0068] The invention can thus be used not only to achieve very high ceramic concentrations (typically greater than 40% by volume and up to 90% by volume), but also to select the first metal matrix specifically for these prefabricated inserts and thus independently of the cast metal (second metal matrix) of the wear part, which is typically cast iron or chrome steel.
[0069] The reactant for producing the infiltrative structure of the aggregated millimeter particles can be selected from ferroalloys, preferably FerroTi, FerroCr, FerroNb, FerroW, FerroMo, FerroB, FerroSi, FerroZr or FerroV. It can also be of the oxide type, preferably TiO 2 ,FeO,Fe 2 O 3 、SiO 2 、ZrO 2 CrO 3 Cr2 O 3 , B 2 O 3 、MoO 3 、V 2 O 5 , CuO, MgO and NiO, or metals or their alloys, preferably iron, nickel, titanium or aluminum on the one hand, and carbon, boron or nitride compounds as a remainder on the other hand, for forming corresponding carbides, borides or nitrides.
[0070] As a non-limiting example, a reaction that can be used to form a "wrap" structure to allow positioning of a preformed ceramic-metal insert in a mold for manufacturing a wear part is generally as follows:
[0071] FeTi+C->TiC+Fe
[0072] TiO 2 +Al+C->TiC+Al 2 O 3
[0073] Fe 2 O 3 +Al->Al 2 O 3 +Fe
[0074] Ti+C->TiC
[0075] Al+C+B 2 O 3 ->B 4 C+Al 2 O 3
[0076] MoO 3 +Al+Si->MoSi 2 +Al 2 O 3
[0077] These reactions can also be combined with one another.
[0078] As mentioned above, the reaction rate can be controlled by moderators in the form of various additives of metals, alloys or particles (e.g., alumina-zirconia particles) that do not participate in the reaction. These additives, when they are reactants, can further be used to advantageously modify the toughness or other properties of the in situ formed structure as desired. This is represented by the following exemplary reaction:
[0079] Fe 2 O 3 +2Al+xAl 2 O 3 ->(1+x)Al 2O 3 +2Fe
[0080] Ti+C+Ni->TiC+Ni
[0081] As non-limiting examples, the pre-fabricated geometric ceramic inserts may be made of titanium carbide, titanium nitride, titanium carbonitride, chromium carbide, chromium nitride, chromium carbonitride, niobium carbide, or tungsten carbide, alone or in admixture.
[0082] The invention improves the performance of the cast reinforced wear parts compared to the wear parts of the prior art, due to the local increase in the wear resistance of the areas reinforced due to the presence of an increased number of wear resistant particles and / or particles of different nature (by means of a more suitable metal matrix). The invention also provides a manufactured wear part with better performance by adding areas of defined geometry and enriched in metal carbides, nitrides, borides or intermetallic alloys and a first metal matrix present before casting the wear part, avoiding preferential wear of the ferrous alloy of the wear part around these areas by alternating a structure of dense areas with fine micro-spherical particles of metal carbides on the millimeter size, for example formed in situ by the SHS process, in the metal matrix of the part in the vicinity of these areas, i.e. in the "wrapping" structure of pre-made ceramic inserts, with areas substantially free of fine micro-spherical particles, while improving the cohesion of these inserts with the ferrous alloy of the reinforced wear part.
[0083] Measurement method
[0084] Average size of particles of metal carbides, nitrides, borides or intermetallic alloys
[0085] The average size d of the particles of metal carbides, nitrides, borides or intermetallic alloys is calculated by the following steps: 50 .
[0086] First, a microphotographic panorama of a polished cross section of the sample is made so that at least 250 intact particles are present in the entire field of view. This panorama is achieved by stitching (the process of combining a series of digital images of different parts of an object into a panorama of the entire object to maintain good clarity) using a computer program and an optical microscope (such as the Universal Image Field Panorama obtained by Alicona InfiniteFocus).
[0087] Appropriate thresholding is then performed to segment the image into features of interest (particles) and background at different gray levels.
[0088] If thresholding is inconsistent due to poor image quality, add the manual steps of drawing the particles, scale bar (if any), and image frame on tracing paper, and the step of scanning the tracing paper.
[0089] The Feret diameter (corresponding to the distance between two parallel tangent lines placed perpendicular to the measurement direction such that the entire projection of the particle lies between the two tangent lines) of each particle is measured in all directions by image analysis software (e.g. ImageJ). Fig.10 Displayed in.
[0090] The minimum and maximum Feret's diameters are then determined for each particle in the image. The minimum Feret's diameter is the smallest diameter in the set of Feret's diameters measured for the particle. The maximum Feret's diameter is the largest diameter in the set of Feret's diameters measured for the particle. Particles that touch the edge of the image are ignored in the calculation.
[0091] The average of the minimum and maximum Feret diameters of each particle is taken as the equivalent diameter x. The volume distribution q of the particle size is then calculated based on a sphere of diameter x. 3 (x).
[0092] Average particle size d 50 is the volume weighted average size according to standard ISO 9276-2:2014
[0093] Example
[0094] Comparative Example
[0095] In this example, the resistance of a reinforced part was measured. The part was manufactured similarly to the method disclosed in the prior art (WO2010 / 031663). The prior art describes a composite impactor for an impact crusher comprising an iron alloy reinforced by a three-dimensional structure of millimeter titanium carbide precursor particles on the side most exposed to wear. The wear part was produced by in-situ self-propagating exothermic synthesis. The impactor weighs 52 kg and the volume of the reinforcement is about 0.88 dm 3 .
[0096] To assess the degree of wear, the overall weight loss of the impactor is measured. In practice, this is the only way to determine wear, which depends on a number of factors, in particular the positioning geometry of the reinforcement in the impactor. Although the impactor wears mainly on the reinforcement side, it also wears partially outside the reinforcement, depending on the positioning. Figure 8 and Fig. 9 A comparison of the corresponding wear between an impactor according to the prior art and an impactor according to the invention is shown.
[0097] In the three-dimensional structure of the reinforcement according to the prior art, there is a periodic alternation between millimeter particles and gaps. The particles contain a mixture of titanium powder with an average particle size of 60 μm and a minimum purity of 98%, graphite powder with a particle size of less than 30 μm and a purity of about 99%, and steel powder with a particle size of less than 60 μm as a reaction moderator. These millimeter particles with a diameter of about 2.5 mm are compacted with a porosity of less than 20%. The following table gives the chemical composition of such particles for 100 kg of particles.
[0098]
[0099] This comparative example thus has a section reinforced with titanium carbide produced solely by in-situ self-propagating thermal synthesis of titanium and carbon used to form titanium carbide during casting. The reaction is initiated by casting an iron alloy consisting of a martensitic stainless steel of the 12CrMoV type, which is further used in the examples according to the invention.
[0100] The wear part thus comprises only a three-dimensional structure of alternating areas of high and low concentrations of titanium carbide produced in situ on the most stressed side of the wear part during casting, without initially including an insert of a ceramic-metal composite material, for example of cylindrical type, preformed in a metal matrix different from the ferrous alloy used for casting. At the end of these steps, a total reinforcement volume of 0.88 dm 3 The weight loss observed during the wear test on the composite impactor for the impact grinder was 3.63 kg per 100 hours of operation (kg / 100 h). For the examples according to the invention, the same conditions of use and materials to be ground were repeated.
[0101] According to the embodiment of the present invention
[0102] Embodiment 1:
[0103] The reinforcing part according to the invention comprises a reinforcing area with a predetermined geometry and a ceramic insert, which is previously manufactured in a size of several centimeters and pre-inserted into a permeable structure containing the reactants required to form the ceramic by a self-propagating exothermic reaction during the casting process. The permeable structure is composed of an aggregate of millimeter particles with an average size of about 2.5 mm containing the reactants required for the reaction. The particles are aggregated in a three-dimensional structure according to a predetermined shape using an organic binder such as a phenolic resin. In this three-dimensional structure, there is a periodic alternation between millimeter particles and gaps. This configuration is Figure 7 Displayed in.
[0104] These particles consist of a mixture of titanium powder with an average particle size of 60 μm and a purity of 98%, graphite powder with an average particle size of 30 μm and a purity of 99%, and steel powder with an average particle size of 60 μm and containing 45CrMoV67 type steel powder as a reaction moderator. These millimeter particles are compacted with a porosity of less than 20%. The following table gives the chemical composition of such particles for 100 kg of particles.
[0105]
[0106] The prefabricated ceramic inserts have a cylindrical geometry. These prefabricated ceramic inserts have a diameter of 12 mm and a height of 20 mm. They consist of 70-80% titanium carbide, 1-3% chromium carbide and a binder containing austenitic manganese steel of the DIN 1.3401 type. This binder forms the first metal matrix.
[0107] The pre-fabricated 67 ceramic inserts were positioned vertically in a predetermined manner in the resin mould, before adding the reactive millimetre particles intended for a self-propagating exothermic reaction and to be aggregated by an organic binder, which defined the reinforcement areas by cut-outs in the resin mould.
[0108] At the end of these steps, a total volume of 0.88 dm was produced by casting an alloy of the 12CrMoV type having the following composition 3 Similar to Figure 2 The three-dimensional structure of the alloy comprises: 0.15-0.20% C; 9.00-11.00% chromium; 0.60-1.10% Mn and 0.35-0.65% Si. The alloy forms a second metal matrix.
[0109]
[0110] Example 2 :
[0111] Example 1 was repeated, but this time before adding the reactive millimetre particles intended for a self-propagating exothermic reaction and to be aggregated by the same organic binder, 77 previously manufactured ceramic inserts were positioned in a predetermined manner in the resin mould, which defined the reinforcement areas by cut-outs in the resin mould. At the end of these steps, a total volume of 0.88 dm 3 Similar to Figure 2 three-dimensional structure.
[0112] The prefabricated ceramic insert consists of 70-80% titanium carbide, 1-3% chromium carbide and a binder as a first metal matrix based on an austenitic manganese steel of the DIN 1.3401 type.
[0113]
[0114] Example 3 :
[0115] Example 1 was repeated using 67 inserts, but this time the prefabricated ceramic inserts contained 75-85% titanium carbonitride and a binder which, as first metal matrix, was based on a nickel and chromium alloy of the DIN 2.4771 type.
[0116]
[0117] Example 4 :
[0118] This concerns an example of a precursor particle system using self-propagating exothermic synthesis (SHS): Ti+V+C.
[0119] These particles consist of a mixture of titanium powder with an average particle size of 60 μm and a purity of 98%, vanadium powder with a particle size of less than 200 mesh, and graphite powder with a particle size of less than 30 μm and a purity of 99%. These particles are compacted with a porosity of less than 22%. The chemical composition of these particles is shown in the following table.
[0120] titanium carbon vanadium 67.01kg 31.23kg 71.32kg
[0121] Example 1 was repeated, likewise using 67 inserts of the same size, but the prefabricated ceramic inserts now contained 70-80% chromium carbide and a binder which, as first metal matrix, was based on a nickel and chromium alloy of the DIN 2.4771 type.
[0122]
[0123] Example 5 :
[0124] This involves an example of a precursor particle system using self-propagating exothermic synthesis (SHS): Ti+V+B 4 C.
[0125] These particles consist of a mixture of titanium powder with a particle size of about 60 μm and a purity of 98%, boron carbide powder with a particle size of less than 150 mesh, and graphite powder with an average particle size of 30 μm and a purity of 99%.
[0126] The particles were compacted with a porosity of less than 22%. The chemical composition of the particles is shown in the table below.
[0127] titanium carbon Boron Carbide 20.10kg 16.01kg 7.736kg
[0128] The 67 prefabricated ceramic inserts contained 80-90% chromium carbide and a binder which, as a first metal matrix, was based on a nickel and chromium alloy of the 2.4771 type.
[0129]
[0130] Example 6 :
[0131] This concerns an example of a precursor particle system using self-propagating exothermic synthesis (SHS): Ti+C is surrounded by non-reactive alumina-zirconia particles to moderate the self-propagating exothermic reaction.
[0132] The precursor particles comprise a mixture of titanium powder with an average particle size of about 60 μm and a purity of 98% and graphite powder with an average particle size of 30 μm and a purity of 99%. These millimeter precursor particles of about 2.5 mm are compacted with a porosity of less than 20%. The chemical composition of these particles of 100 kg of particles is given in the table below.
[0133] titanium carbon 60 / 39 / 0.15 Alumina-Zirconia / Titanium Oxide as a moderator 63.95kg 16.05kg 20.00kg
[0134] The non-reactive particles contain alumina-zirconia, with alumina accounting for 60%, zirconium oxide accounting for 39%, and titanium oxide accounting for 0.15%.
[0135] The average size of these non-reactive millimetric particles was 2.1 mm.
[0136] The prefabricated ceramic insert consists on average of 70-80% titanium carbide, 1-3% chromium carbide and a binder based on austenitic manganese steel of the DIN 1.3401 type, constituting the first metal matrix.
[0137] Compared with the exothermic reaction precursor particles, the weight proportion of the non-reactive particles can vary between 5% and 40% by volume, preferably between 10% and 30%, more preferably between 15% and 20%. In this embodiment, the proportion is 20% by weight.
[0138]
[0139] Summary tables and interpretation of results
[0140] The table below shows the weight loss of a 52kg impactor in its new state, with a reinforced volume of approximately 0.88dm 3 The weight loss was measured after 696 hours of operation and decreased to 100 hours of operation.
[0141]
[0142] Interpretation of results.
[0143] The wear performance of each example is a combination of the wear rates of the reinforcement surrounding the preformed insert, the preformed insert itself and the unreinforced areas of the impactor. The wear rates of these different areas have therefore been evaluated to explain the performance differences among the examples.
[0144] The table below shows the wear rate of the different parts in kg per 100 hours of operation.
[0145]
[0146] The table shows that the wear rate of the preformed insert depends on its characteristics, and the performance of the preformed inserts in the previous examples is classified as follows (from best to worst performance):
[0147] a) 75-85% titanium carbonitride and a nickel alloy based binder
[0148] b) 70-80% titanium carbide, 1-3% chromium carbide and an austenitic steel type binder
[0149] c) 70-80% chromium carbide and nickel-based binder
[0150] d) 80-90% chromium carbide and nickel-based binder
[0151] In fact, the wear resistance of ceramic-metal composites depends on the properties of the ceramic particles, their proportion and distribution, and the nature of the binder used.
[0152]
[0153] Without scientifically rigorous explanations, it is generally believed that there is a relationship between the performance of different ceramic-metal composites used as preform inserts and the elastic modulus of the constituent hard particles. In fact, it is known that the more the elastic modulus of a particle increases, the more its impact resistance increases, since the deformation of the particle under equivalent stress decreases. The following figure shows this relationship:
[0154]
[0155] This also means that chromium carbides are more brittle than titanium-containing carbides or carbonitrides, which explains the lower performance of Example 5 compared to Example 4, despite the higher percentage of chromium carbide in its preformed insert.
Claims
1. A wear part (1) comprising a reinforcement (2) comprising an iron alloy reinforced with metal carbides, nitrides, borides or intermetallic compounds, wherein the reinforcement (2) comprises an insert (3) having a predetermined geometry, the insert (3) comprising ceramic microparticles of metal carbides, nitrides, borides or intermetallic compounds prefabricated and encapsulated in a first metal matrix (10), the insert (3) being inserted into the reinforcement (2), the reinforcement (2) having a macro-microstructure of alternating millimeter areas (5) with a high concentration of micrometer-sized spherical particles (7) of metal carbides, nitrides, borides or intermetallic compounds and millimeter-sized areas (4) with almost no micrometer-sized spherical particles (7) of metal carbides, nitrides, borides or intermetallic compounds, the iron alloy forming a second metal matrix (6), the second metal matrix (6) being different from the first metal matrix (10), and The wear part (1) is manufactured according to a method comprising the following steps: - providing a mould comprising a cavity of a wear part (1) having a predetermined geometry of the area to be reinforced; - introducing and positioning in the zone to be reinforced an intimate mixture of powders in the form of millimeter-grains for reaction in a self-propagating exothermic reaction in the form of millimeter-grains of precursors of metal carbides, nitrides, borides or intermetallic compounds, optionally mixed with a moderating powder, and at least partially surrounding one or more prefabricated inserts (3) having a defined geometry and enriched in metal carbides, nitrides, borides or intermetallic compounds and comprising a first metal matrix (10); - pouring a liquid iron alloy into the mould, said liquid iron alloy initiating said self-propagating exothermic reaction resulting in the formation of metal carbides, nitrides, borides or intermetallic compounds in said precursor millimetre pellets.
2. Wear part (1) according to claim 1, wherein the metal used for the ceramic microparticles of the insert (3) is titanium.
3. Wearing part (1) according to claim 2, wherein the insert (3) mainly comprises ceramic microparticles of titanium carbide.
4. Wear part (1) according to claim 1, wherein the insert (3) comprises a concentration of metal carbides, nitrides, borides or intermetallic compounds of up to 90% by volume and at least 30% by volume.
5. Wear part (1) according to claim 1, wherein the insert (3) comprises a concentration of metal carbides, nitrides, borides or intermetallic compounds of up to 90% by volume and at least 40% by volume.
6. Wear part (1) according to claim 1, wherein the insert (3) comprises a concentration of metal carbides, nitrides, borides or intermetallic compounds of up to 90% by volume and at least 50% by volume.
7. Wear part (1) according to claim 1, wherein the first metal matrix (10) incorporating the ceramic microparticles of the insert (3) mainly comprises nickel, a nickel alloy, cobalt, a cobalt alloy or an iron alloy different from the casting alloy constituting the second metal matrix (6).
8. The wearing part (1) according to claim 1, wherein the insert (3) comprises an average dimension D 50 Particles of metal carbides, nitrides, borides or intermetallic compounds smaller than 80 µm (9).
9. The wearing part (1) according to claim 1, wherein the insert (3) comprises an average dimension D 50 Particles of metal carbides, nitrides, borides or intermetallic compounds smaller than 60 µm (9).
10. The wearing part (1) according to claim 1, wherein the insert (3) comprises an average dimension D 50 Particles of metal carbides, nitrides, borides or intermetallic compounds smaller than 40 µm (9).
11. Wear component (1) according to claim 1, wherein the insert (3) and the millimeter region (5) of micrometer spherical particles (7) with a high concentration of metal carbides, nitrides, borides or intermetallic compounds comprise micrometer gaps containing different metal matrices (6, 10).
12. Wear part (1) according to claim 1, wherein the reinforcement (2) consists of alternating millimeter areas (5) with a high concentration of micrometer-sized spherical particles (7) of metal carbides, nitrides, borides or intermetallic compounds produced by the aggregation of reacted reactants and millimeter areas (4) with almost no micrometer-sized spherical particles (7) of metal carbides, nitrides, borides or intermetallic compounds, forming millimeter-sized gaps infiltrated by the second metal matrix, i.e. the casting metal.
13. The wearing part (1) according to claim 1, wherein the reinforcing portion (2) further comprises millimeter particles of aluminum oxide, zirconium oxide or an aluminum oxide-zirconium oxide alloy.
14. The wearing part (1) according to claim 1, which is manufactured in the form of an impactor, an anvil, a cone or a grinding roller.
15. Method for manufacturing a wearing part (1) according to any one of the preceding claims, comprising the following steps: - providing a mould comprising a cavity of a wear part (1) having a predetermined geometry of the area to be reinforced; - introducing and positioning in the zone to be reinforced an intimate mixture of powders in the form of millimeter-grains for reaction in a self-propagating exothermic reaction in the form of millimeter-grains of precursors of metal carbides, nitrides, borides or intermetallic compounds, optionally mixed with a moderating powder, and at least partially surrounding one or more prefabricated inserts (3) having a defined geometry and enriched in metal carbides, nitrides, borides or intermetallic compounds and comprising a first metal matrix (10); - casting a liquid iron alloy into a mold, said liquid iron alloy initiating said self-propagating exothermic reaction resulting in the formation of metal carbides, nitrides, borides or intermetallic compounds in said precursor millimeter particles; - forming in the reinforced region of the wear part an alternating macro-microstructure of periodic millimeter areas of micrometer-sized spherical particles (7) respectively enriched and depleted in metal carbides, nitrides, borides or intermetallic compounds, infiltrated by a second metal matrix (6) produced by casting, said alternating macro-microstructure as a whole at least partially surrounding the one or more inserts (3).
16. Method for producing a wearing part (1) according to claim 15, wherein the insert (3) having a predetermined geometry produced before casting the wearing part is produced by powder metallurgy.
17. The method of claim 15, wherein the intimate mixture of powders for reaction in the form of millimeter pellets in a self-propagating exothermic reaction consists of carbon, titanium, a binder and optionally a moderating powder.
Citation Information
Patent Citations
Cast part with enhanced wear resistance
WO2003047791A1
Composite tooth for working the ground or rock
WO2010031660A1
Hierarchical composite material
WO2010031662A1
Composite impactor for percussion crushers
WO2010031663A1
Hierarchical composite material
EP2334836B1